Application of DNA barcoding for identifying forensically relevant Diptera from northern Thailand - Barbara Karolina Zajac (2018)
© 2016, Springer-Verlag Berlin Heidelberg. In recent decades, forensic entomology has become a useful tool in criminal investigations all over the world. Species-specific identification of flies plays an important role in this field and is obligatory for accurate calculation of the post-mortem interval. However, not all important colonizers of a corpse can be identified by common morphological keys. Due to similar morphology and the lack of keys for some taxa, especially for immature stages, DNA barcoding has become more popular during the last recent years. This development is particularly important for countries like Thailand, in which forensic entomology is a newly developing research area and which faces several challenges such as a high biodiversity of fly species. The most commonly used barcoding region in forensic entomology, the mitochondrial cytochrome oxidase subunit 1 (coI) gene, as well as a 1000-bp-long region of the 28S nuclear rRNA gene, was used to analyze and establish the molecular barcodes of 13 different species of flies of forensic relevance in northern Thailand.